AGW610- Finance & Accounting For Management (September 1997) - PPP, Pusat Pengajian Pengurusan (1997)
Master of Business Administration First Semester Examination Academic Session 1997 / 98 September 1997 AGW610- FINANCE & ACCOUNTING FOR MANAGEMENT Time : [3 hours] INSTRUCTIONS: Please make sure that this examination paper consists of EIGHT (8) printed pages before you begin. Answer FOUR (4) questions.